Principles for Pareto Efficient Border Carbon Adjustment - Michael Keen; Christos Kotsogiannis (Center for Economic Studies and ifo Institute (CESifo), 2024)
Border Carbon Adjustment Mechanisms (BCAMs) are becoming reality in the EU and elsewhere, and recur—in very different form—in U.S. legislative proposals. But they remain contentious, with features and differences that leave the underlying welfare rationale and implications unclear. Exploring these, this paper establishes two general principles for Pareto efficient BCAM design: regulatory measures should be recognized symmetrically with explicit carbon prices; and, whatever the ambition of mitigation in the BCA-imposing country, a general 'difference-in-differences' form of a BCAM is appropriate. These nest, as special cases, the very different approaches to BCAM design in Europe and the U.S.
Keywords: H21; H23; H87; F18; 330; environmental taxation; carbon pricing; border tax adjustment; international taxation